2012
DOI: 10.1097/hjh.0b013e32835a27b3
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and renal excretion of potassium in African–Americans and White Americans

Abstract: The racial difference in urinary K(+) handling manifested by decreased excretion of K(+) in African-Americans cannot be attributed to an increase in net gastrointestinal excretion of this cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…This is probably due to the lack of supervision of the diet when participants had their meals off-site, one of the pitfalls of these types of studies. Cumulative K ϩ gastrointestinal excretion was also not different after 9 days of controlled intake, and this result was accompanied by lower rates of excretion in African Americans (594). Because the proximal tubule and thick ascending limb reabsorb 85% of the filtered K ϩ and only the thick ascending limb reabsorbs it actively, differences in K ϩ excretion before individuals reach balance could be due to a defect increasing the activity of the thick ascending limb.…”
Section: A Racial Differencesmentioning
confidence: 84%
“…This is probably due to the lack of supervision of the diet when participants had their meals off-site, one of the pitfalls of these types of studies. Cumulative K ϩ gastrointestinal excretion was also not different after 9 days of controlled intake, and this result was accompanied by lower rates of excretion in African Americans (594). Because the proximal tubule and thick ascending limb reabsorb 85% of the filtered K ϩ and only the thick ascending limb reabsorbs it actively, differences in K ϩ excretion before individuals reach balance could be due to a defect increasing the activity of the thick ascending limb.…”
Section: A Racial Differencesmentioning
confidence: 84%
“…Potassium as a supplemental salt was retained the most efficiently, reflecting higher net absorption efficiency. Of the seven trials examined by the 2019 DRI committee, potassium intake level of approximately 56 mmol/d or 2200 mg/d or greater resulted in a positive balance [ 20 , 21 , 22 , 23 , 24 , 42 ] levels of 54 mmol/d or 21 mg/d or less resulted in a negative balance [ 22 , 24 ], and one study reported neutral balance at an intake of 52 mmol/d or 2034 mg/d [ 43 ]. Our study evaluated potassium intake levels above 59 mmol/d or 2300 mg/d and resulted in positive potassium balance in all phases.…”
Section: Discussionmentioning
confidence: 99%
“…Only seven studies with assessment of complete intake, urinary, and fecal losses were available to the DRI committee. These studies showed an increase in urinary potassium with increasing intake (primary mode of excretion) [ 20 ], fecal losses averaging approximately 10.7 mmol/d (420 mg/d)) at intakes ranging from 59 to 100 mg/d (2300 to 3900 mg/d) [ 21 , 22 , 23 ], as well as variable losses due to sweat [ 24 , 25 , 26 , 27 , 28 ]. Given the limited number and overall heterogeneity in study design and findings, the committee concluded that there was insufficient evidence to establish potassium intake recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…With a supplementation of 40 mmol KCl per day (the amount of potassium in approximately four bananas) the average urine potassium excretion increased from 72 to 107 mmol/day. This translates to a dietary intake of approximately 120 mmol/day when considering approximately 10% fecal potassium loss 40 and is therefore at the higher end of the current dietary reference values (90-120 mmol/day). 14,15 Potassium supplementation was associated with a rise in the plasma potassium concentration of on average 0.4 mmol/L.…”
Section: Discussionmentioning
confidence: 99%